The Importance of Image in Teaching a Foreign Language: Enhancing Foreign Language Learning through the Use of Images (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present paper aims to study the importance of images in teaching a foreign language to the learners learning a foreign language. Using books as a study material is the traditional method which is being followed in the classrooms across the world.In the recent years, researches made by language specialists confirms that learning a foreign language is easier and interesting if a psychological approach is adapted while a foreign language is being taught to learners of that language .Most of the learners appreciate classes where they involve themselves in learning through activities rather than traditional methods .Since the activities pushes the students and motivates them to learn in unconventional ways, the teachers are also motivated to find new methods in learning. This paper proves that the use of images help learners learning a foreign language in an easy and efficient way.